Edukasi Penggunaan Obat Vitamin D (Kalsiferol) untuk Menjaga Kesehatan Tulang dan Gigi pada Remaja disertai Literasi Biaya Kesehatan di Kecamatan Pogalan - Fendy Prasetyawan; Yuneka Saristiana; Mohammad Firdaus Alshol; Herman Herman; Novyananda Salmasfattah; Lisa Savitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2026)
Bone and dental health in adolescents are strongly influenced by adequate vitamin D intake; however, knowledge regarding its proper use remains limited, particularly in semi-urban areas. This community service activity aimed to improve adolescents’ understanding of rational vitamin D (calciferol) use accompanied by basic health-cost literacy education. The program was conducted on March 17, 2026, in Pogalan District and involved 12 adolescents. The study used a pre-experimental design with a one-group pretest–posttest approach. The intervention was carried out through interactive education covering the clinical aspects of vitamin D, rational drug use, and a simple introduction to preventive and curative costs related to vitamin D deficiency. Data analysis was performed using a paired sample t-test to compare knowledge scores before and after the intervention. The results showed a significant increase in knowledge scores after the intervention (p < 0.05), indicated by a shift in knowledge levels from low and moderate categories to predominantly high categories. These findings indicate that the integration of health education with health-cost literacy can support the improvement of adolescents’ understanding regarding the rational use of vitamin D. In conclusion, the educational intervention was effective in improving adolescents’ knowledge regarding the rational use of vitamin D.